THE EFL TEACHERS’ BELIEFS AND THEIR TEACHING PRACTICES - Diana Nur Utami (OKARA: Jurnal Bahasa dan Sastra, 2016)
This paper tries to discuss the relationship between the EFL teachers’ beliefs and their teaching practice. It is interesting to note that practically being exposed to the same materials, curriculum, students and environment, teachers conduct their teaching in varied ways. It can be seen from how students receive and build their image about their teachers. It also reflects the effectiveness of the practice they do. Therefore, it will be very useful to understand whether their teaching practice, including class and curriculum management, is influenced by their beliefs or not. This article embraces the theoretical review and previous studies conducted in this field.  This will lead to how teachers should understand about themselves and their profession, consecutively they will be able to develop their competence through activities that can enhance their positive beliefs which will enlighten their teaching practice and maintain effective teaching practice in their classroom.